Cytotaxonomy of the Simuliidae (Diptera): a systematic and bibliographic conspectus - Adler, Peter H.; Crosskey, Roger W. (Zootaxa, 2015)
An annotated compilation of all chromosomal works (cytoconspectus) on the Simuliidae is presented, covering 577 species including 541 formally named species—24.8% of the world’s extant nominal species—and 36 formally unnamed species. The first published record of polytene chromosomes in a simuliid appeared in 1919, followed by an imposing body of chromosomal research, most notably since 1956. The bibliography assembled here includes 653 works containing novel chromosomal information on the Simuliidae. Cytotaxonomy of the Simuliidae began in 1951 in the Canadian laboratory of Klaus Rothfels and subsequently expanded worldwide. Although chromosomal study has been uneven across species, it has provided a rich database of the genetics of natural populations and much of the foundation for the modern taxonomy and systematics of the family. After peaking in the late 1980s, cytotaxonomic productivity became more sporadic as the molecular movement gained popularity, despite the potential that an integrated chromosomal and molecular approach holds.